Fatal complication after transsphenoidal surgery of pituitary adenoma: case report - Conceição Aparecida Dornelas; Tereza N. A. G. Nogueira; Evandro T. Alves; River A. B. Coêlho (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT The objective of this study was to report a rare fatal complication in the postoperative period of transsphenoidal surgery of the pituitary gland (adenoma), with a brief review of the subject. The patient was a 54-year-old white man with acromegaly and severe heart failure, who after microsurgery developed blood pressure instability within 32 hours after the procedure and died. The autopsy revealed: hypertrophy and ventricular dilation with myocarditis, pericarditis and myocardial fibrosis; mesenteric ischemia with transmural coagulation necrosis of the intestinal loops; acute tubular necrosis; and hepatic steatosis. The findings are consistent with cardiogenic shock and abdominal sepsis due to necrosis of the intestinal loops.